Peran Guru Ilmu Pengetahuan Sosial dalam Meningkatkan Keaktifan Sosial Siswa Kelas XI di MA Al Muslihun Tunggangri Kalidawir Tulungagung - Muhamad Niko Dardiri Pratama; Jani Jani (Pusat Riset dan Inovasi Nasional, 2026)
Education plays a crucial role in shaping individuals who are able to contribute positively to society. Teachers, particularly in Social Studies (Ilmu Pengetahuan Sosial/IPS), have a strategic role in fostering students’ social activity and character development. At MA Al Muslihun Tunggangri Kalidawir Tulungagung, IPS teachers face several challenges, including a dense curriculum, limited facilities, and varying levels of student interest. This study aims to analyze the role of IPS teachers in enhancing the social activity of eleventh-grade students, examine the processes implemented, and identify the supporting and inhibiting factors encountered in the learning process. This research employed a descriptive qualitative approach. Data were collected through observation, in-depth interviews, and documentation. Observations focused on the IPS learning process and students’ social interactions, while interviews were conducted with teachers and relevant participants to gain deeper insights. Documentation included written and visual records related to students’ social activities and instructional practices. The findings indicate that IPS teachers play a significant role in promoting students’ social activity through participatory, collaborative, and contextual learning methods. Teachers integrate current social issues into classroom discussions and encourage group work, discussions, and social projects to develop values such as cooperation, empathy, responsibility, and critical thinking. Despite challenges such as low student motivation and limited resources, teachers address these issues by utilizing extracurricular activities and adaptive teaching strategies. The study is expected to contribute to educational innovation and serve as a reference for improving effective and socially oriented teaching practices.